2018
DOI: 10.1016/j.ajhg.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Mutations in the Mitochondrial Ribosomal Protein MRPS2 Cause Sensorineural Hearing Loss, Hypoglycemia, and Multiple OXPHOS Complex Deficiencies

Abstract: Biogenesis of the mitochondrial oxidative phosphorylation system, which produces the bulk of ATP for almost all eukaryotic cells, depends on the translation of 13 mtDNA-encoded polypeptides by mitochondria-specific ribosomes in the mitochondrial matrix. These mitoribosomes are dual-origin ribonucleoprotein complexes, which contain mtDNA-encoded rRNAs and tRNAs and $80 nucleus-encoded proteins. An increasing number of gene mutations that impair mitoribosomal function and result in multiple OXPHOS deficiencies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 32 publications
4
55
0
Order By: Relevance
“…Translation in mitochondria is carried out by specialized mitoribosomes that are structurally distinct with 2-fold reduced mt-rRNA and ~1 MDa increased protein mass. Specific autosomal recessive mutations associated with these extra proteins cause severe, infantile onset disease with growth retardation, neurological phenotypes and cardiac involvement, and are associated with Perrault syndrome ( De Silva et al, 2015 ; D'Souza and Minczuk, 2018 ; Boczonadi et al, 2018 ; Gardeitchik et al, 2018 ; Bugiardini et al, 2019 ). Analysis of individuals with variations in mitoribosomal proteins demonstrated that mutations result in Leigh syndrome ( Lake et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Translation in mitochondria is carried out by specialized mitoribosomes that are structurally distinct with 2-fold reduced mt-rRNA and ~1 MDa increased protein mass. Specific autosomal recessive mutations associated with these extra proteins cause severe, infantile onset disease with growth retardation, neurological phenotypes and cardiac involvement, and are associated with Perrault syndrome ( De Silva et al, 2015 ; D'Souza and Minczuk, 2018 ; Boczonadi et al, 2018 ; Gardeitchik et al, 2018 ; Bugiardini et al, 2019 ). Analysis of individuals with variations in mitoribosomal proteins demonstrated that mutations result in Leigh syndrome ( Lake et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This analysis revealed significant assembly defects of all complexes whose biogenesis depends on the synthesis of the 13 mtDNA‐encoded subunits in mitochondria (Figure b and c). Moreover, we observed an accumulation of the F1 subcomplex of complex V indicative of a biogenesis defect of this OXPHOS complex (Gardeitchik et al., ; Metodiev et al., ).…”
Section: Resultsmentioning
confidence: 72%
“…This dearth of information about mitochondrial protein synthesis and proteostasis in synapses is in stark contrast with the numerous human mutations affecting mitochondrial protein synthesis and degradation. These mutations associate with pathology ranging from epileptic encephalopathy to neurodevelopmental and psychiatric disorders, which are also frequent phenotypes in mutations affecting bona fide synaptic genes (Akbergenov et al, 2018;Gardeitchik et al, 2018;Lake et al, 2017;Lightowlers et al, 2015;Nimmo et al, 2019;Pei and Wallace, 2018;Shutt and Shadel, 2010;Wallace et al, 2010). Here we make a case for mitochondrial protein translation and proteostasis in synapse biology focusing on genes encoded in a neurodevelopmental risk mutation, the 22q11.2 microdeletion syndrome locus…”
Section: Discussionmentioning
confidence: 99%